The strategy to enhance the shariah financial literacy and inclusion in Indonesia (Case study at financial services authority office in the city of Malang) - Luthfiansyah, Muhammad; Khotiawan, Ma’rufa (MEC-J (Management and Economics Journal), 2017)
The results of the survey of literacy and Financial Inclusion Shari'ah in Indonesia 2016 each show numbers 8.11 %  and 11.06 %. Whereas the inhabitants of the religion of Islam in Indonesia more than 85%. With this then needs to be formulated strategies that can increase the level of literacy and financial inclusion shari'ah in Indonesia. The importance of literacy improvement and Financial Inclusion Shari'ah to improve the behavior of the community in financial management and to improve the welfare of them. So that priorities are intended to know how the strategy applied to increasing literacy and Financial Inclusion Shari'ah. This research uses qualitative research method with the approach of the case study. The results of this research are some government policy that is contained in the form of National Strategy for Financial Literacy Indonesia (SNLKI) to improve financial literacy Shari'ah and inclusive Financial National Strategy (SNKI) to improve financial inclusion. But the next research needs to examined and monitored about various programs to increase shari'a literacy and financial inclusion is doing by the government.Keywords: Sharia Financial Literacy, Sharia Financial Inclusion, the strategy.